Gastroesophageal Reflux Disease, Tooth Erosion, and Prosthodontic Rehabilitation: A Clinical Report - Ned B. Van Roekel, DDS, MSD (Journal of Prosthodontics, 2003)
Gastroesophageal reflux disease (GERD) is a relatively common gastrointestinal disorder in the United States